Uncovering cell biology in the third dimension - Robertson, Gabriella L. (Mol Biol Cell, 2020)
Developmental biology has long benefited from studies of classic model organisms. These model systems have provided the fundamental understanding of general principles of development, as well as insight into genes and signaling pathways that control unique aspects of cell fate specification and tissue morphogenesis. Because human brain development cannot be studied in vivo, scientists have relied on these model systems to study basic principles underlying the development of this complex organ as many of these genes and signaling pathways play conserved roles in human development. However, recent studies have shown species-specific signatures in neurodevelopment such as the transcriptome of outer-radial glia, suggesting use of a human-derived model remains imperative. Over the past decade, human stem cell-derived brain organoids have emerged as a biologically relevant model system to study normal human brain development and neurological diseases. Here, we provide a historical perspective of this emerging model system, discuss current systems and limitations, and propose that new mechanistic insight into cell biology can be revealed using these three-dimensional brain structures.